INDETERMINACY AND THE POLITICAL ECONOMY: CLS, LEGAL POLITICS, AND DEFETISHIZING THE LPE DEBATE. - RASULOV, AKBAR (Law & Contemporary Problems, 2026)
The article focuses on the Critical Legal Studies (CLS) tradition’s critique of mainstream Law and the Political Economy (LPE) thought, emphasizing the concept of legal indeterminacy and its implications for legal politics and reformist practice. CLS scholars argue that the relationship between law (L) and the political economy (PE) is fundamentally indeterminate both externally—due to the porous, unstable transmission between legal rules and economic outcomes—and internally—because legal interpretation itself is open-ended and contingent on collective legal work and struggle. This indeterminacy challenges the mainstream LPE tradition’s technocratic and deterministic model, which assumes stable “laws of motion” governing legal-economic interactions and the feasibility of a science of regulatory design. Instead, CLS proposes a phenomenological and anti-reificationist approach, viewing (in)determinacy as a shared intersubjective experience shaped by organized groups of legal actors who engage in ongoing interpretative work to influence legal meaning and political outcomes. The article suggests that CLS’s integrated theory offers valuable insights for contemporary legal scholars and activists by highlighting the limits of legal determinacy, the centrality of human agency, and the potential for lawyer-led progressive interventions within the political economy.